Velocity Control Of A Car-Like Mobile Robot - Top , Sokunphal (2017)
The velocity control is a very important component for every mobile robot. This velocity control will provide a stable velocity to the system, and increase the ability of calculation the movement coordinate of the mobile robot. Meanwhile, the velocity control of a car-like mobile robot is a main title in this dissertation. The main purpose of the velocity control of a car-like mobile robot is to design speed controller and apply the car-like robot kinematic model in order to obtain the current movement coordinate of the robot. There are some procedures to achieve the objective of this project such as to verify DC motor model, design the speed controller based on PI controller, and implement with car-like robot kinematic model. The DC motor model can be verified based on real-time experiment. The speed controller can be designed by using PI controller. However, the critical part of speed controller is to calculate the PI parameters. The car-like robot kinematic model is used to define the current movement coordinate of the robot based on the linear velocity from speed controller, and the fixed steering angle is set to be 30o. Moreover, this fixed 30o steering angle is made the robot turn left for 30o. By doing the simulation and real-time testing for the proposed methods, the final result can be obtained. The speed controller is successfully designed which provides a stable velocity to the system. The car-like robot kinematic model is also successfully implemented on the robot, but the improvement of this model is needed in order to make it more accurate.